The impact of COVID-19 on sexual behavior, HIV prevention interest, general healthcare access, and other HIV risk factors among trial participants in Malawi, South Africa, Uganda, and Zimbabwe - Mancuso, Noah; Mathebula, Florence; Chitukuta, Miria; Matambanadzo, Kudzai V.; Tenza, Siyanda; Reddy, Krishnaveni; Nobula, Lumka; Kemigisha, Doreen; Stoner, Marie C. D. (Frontiers in Reproductive Health, 2023)
Introduction The COVID-19 pandemic greatly impacted HIV prevention and care globally. The pandemic also had disproportionate impacts on the financial, emotional, and physical wellbeing of women and girls in East and Southern Africa, who were already at increased HIV vulnerability. This study aimed to understand how the COVID-19 pandemic and its response efforts impacted the sexual behavior, HIV prevention interest, general healthcare access, and other HIV risk factors of women and girls in HIV prevention studies. Methods Using the socio-ecological model (SEM), an explanatory sequential mixed-methods analysis was performed with data from four Microbicide Trial Network (MTN) studies on different populations—adolescent girls and young women (AGYW), pregnant persons, breastfeeding persons, and couples—in Malawi, South Africa, Uganda, and Zimbabwe. Descriptive statistics for outcomes of interest were calculated within each study separately and Chi-squared tests of independence were performed to evaluate associations between study population and outcomes. Excerpts from study qualitative interviews were stratified into code reports which were then summarized into memos with key themes and considerations of the SEM framework to provide context to quantitative findings. Results Few participants (8/731) had known or suspected COVID-19 infection. Sexual frequency and alcohol use decreased most often among AGYW compared to pregnant or breastfeeding women and couples (p-value < 0.001). The pandemic had little impact on changes in reported HIV prevention interest or access to HIV prevention study products. Healthcare access was impacted for everyone, with couples most likely to report decreases in access (p-value < 0.001). From qualitative interviews, economic instability, adverse mental health, and increased violence due to COVID-19 caused increased strain on other factors related to HIV vulnerability. Conclusions While interest in HIV prevention did not change and a few HIV risks decreased for most women and girls, other vulnerabilities to HIV increased due to the COVID-19 pandemic, highlighting the importance of continued access to HIV prevention for women and girls. More research is needed to better understand the long-term impact of COVID-19 on HIV prevention and vulnerability in community populations.